Bitcoin As Innovative Technology: Security, and Decentralization - Iskamto, Dedi (ADPEBI, 2024)
Bitcoin is one of the greatest innovations in modern financial technology. Bitcoin allows financial transactions to be conducted without the presence of financial institutions and is run by a decentralized peer-to-peer network. Due to the security and decentralization associated with Bitcoin, this digital currency has attracted the interest of many people around the world. However, behind all of its technological sophistication, Bitcoin also faces several challenges in Indonesia. Some of the problems that Indonesia faces include regulation, volatility, scalability, security, education, environment, and the legality of Bitcoin. The novelty of Bitcoin continues to evolve with the emergence of many new cryptocurrencies that try to address the problems found in Bitcoin, such as Ethereum and Ripple. Nevertheless, Bitcoin remains one of the most stable and popular cryptocurrencies in the world today. The purpose of our paper titled